The Analysis of Parents' Understanding in Understanding Balanced Nutrition in Children : Analisis Pemahaman Orang Tua dalam Pemahaman Gizi Seimbang pada Anak - Hariani Fitrianti; Nur Aisyah Ningtias; Pulung Riyanto; Cristina Normalita de Lima; Diah Hermawati (Journal of Physical and Outdoor Education, 2022)
This study aims to describe the understanding of parents in fulfilling balanced nutrition in group B children of TK Pertiwi XI Merauke. This research is descriptive qualitative research. The research was conducted in group B of TK Pertiwi XI Merauke. The research subjects were Parents, Teachers and Principals of TK Pertiwi XI Merauke. Data collection techniques used are tests, observations, and documentation. The instrument used was a mathematical reasoning ability test sheet and a mathematical connection ability test sheet as well as student and teacher activity observation sheets. The results showed that the fulfillment of children's nutrition activities can be seen from the type of children's food which includes 4 healthy 5 perfect, the child's nutritional needs are quite good consisting of carbohydrates, proteins, vitamins and minerals. This activity is very effective because it makes it easier for children to carry food and become independent. The Pertiwi XI Merauke Kindergarten teacher is quite creative in feeding children. Second, understanding of parents in fulfilling children's nutrition, of course, parents start from parental awareness to support optimal child development through nutrition fulfillment and nutrition fulfillment through child health checks in collaboration with the puskesmas. Teachers and parents must have obstacles to meet the different nutritional needs of children. Broadly speaking, parents already understand about the fulfillment of children's nutrition.